1993
DOI: 10.1161/01.cir.87.2.464
|View full text |Cite
|
Sign up to set email alerts
|

Different secretion patterns of atrial natriuretic peptide and brain natriuretic peptide in patients with congestive heart failure.

Abstract: We conclude that plasma levels of BNP mainly reflect the degree of ventricular overload and that the secretion patterns of ANP and BNP vary with underlying cardiac disorders of CHF with different degrees of overload in atria and ventricles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
323
4
6

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(358 citation statements)
references
References 35 publications
20
323
4
6
Order By: Relevance
“…In addition, the clinical signs of heart failure and physical examination in the dogs with experimental MR were evaluated to be divided into the heart failure classes according to the New York Heart Association (NYHA) Atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) are cardiac hormones responsible for the regulation of body fluid homeostasis and blood pressure [18]. The synthesis and secretion of ANP and BNP have demonstrated to augment in human abnormal heart conditions [19,21]. Plasma ANP and BNP concentrations are therefore good indicators for the severity, the prognosis and the left ventricular (LV) dysfunction in human acute myocardial infarction (AMI) and congestive heart failure (CHF) [12,19].…”
mentioning
confidence: 99%
“…In addition, the clinical signs of heart failure and physical examination in the dogs with experimental MR were evaluated to be divided into the heart failure classes according to the New York Heart Association (NYHA) Atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) are cardiac hormones responsible for the regulation of body fluid homeostasis and blood pressure [18]. The synthesis and secretion of ANP and BNP have demonstrated to augment in human abnormal heart conditions [19,21]. Plasma ANP and BNP concentrations are therefore good indicators for the severity, the prognosis and the left ventricular (LV) dysfunction in human acute myocardial infarction (AMI) and congestive heart failure (CHF) [12,19].…”
mentioning
confidence: 99%
“…In valvular disorders, ANP and BNP levels are affected by the site of valve damage (mitral, aortic, etc), the form of damage (regurgitation, stenosis), the severity of valve dysfunction (regurgitant fraction, effective orifice area), as well as ventricular and atrial function (9)(10)(11)(12)(13). Chronic LV volume overload as a result of MR leads to compensatory dilation of the LV.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies demonstrated a correlation of the plasma BNP level with ventricular dilation in patients with dilated cardiomyopathy (23). Studies in adult patients found plasma BNP to be an accurate predictor of the presence of congestive heart failure (24,25) as well as providing predictive information for use in risk stratification in patients with acute coronary syndromes (26) and chronic heart failure (27).…”
Section: B-type Natriuretic Peptide (Bnp)mentioning
confidence: 99%